2007
DOI: 10.1074/jbc.m702819200
|View full text |Cite
|
Sign up to set email alerts
|

Knock Down of γ-Glutamylcysteine Synthetase in Rat Causes Acetaminophen-induced Hepatotoxicity

Abstract: Drug-induced hepatotoxicity is mainly caused by hepatic glutathione (GSH) depletion. In general, the activity of rodent glutathione S-transferase is 10 to 20 times higher than that of humans, which could make the prediction of drug-induced hepatotoxicity in human more difficult. ␥-Glutamylcysteine synthetase (␥-GCS) mainly regulates de novo synthesis of GSH in mammalian cells and plays a central role in the antioxidant capacity of cells. In this study, we constructed a GSH-depletion experimental rat model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Meanwhile, several studies have reported on the regulation of numerous stimuli on its activity (Soltaninassab et al, 2000;Wild and Mulcahy, 2000;Franklin et al, 2009). GCL is reported to play important roles in regulating AP-induced liver injury, and the enzymatic activity and protein expression of GCL are both decreased after AP administration (Akai et al, 2007;Shinohara et al, 2010). Our results showed that FL prevented AP-induced decrease in GCL enzymatic activity, which may be due to the increased expression of the GCLC protein.…”
Section: Discussionmentioning
confidence: 40%
“…Meanwhile, several studies have reported on the regulation of numerous stimuli on its activity (Soltaninassab et al, 2000;Wild and Mulcahy, 2000;Franklin et al, 2009). GCL is reported to play important roles in regulating AP-induced liver injury, and the enzymatic activity and protein expression of GCL are both decreased after AP administration (Akai et al, 2007;Shinohara et al, 2010). Our results showed that FL prevented AP-induced decrease in GCL enzymatic activity, which may be due to the increased expression of the GCLC protein.…”
Section: Discussionmentioning
confidence: 40%
“…Rodents are less sensitive to APAP-induced acute hepatotoxicity than humans and this species difference is accounted for by differences in glutathione content, glutathione synthesis activity or conjugation activity of glutathione with drug metabolites in the liver between rodents and humans (Grover and Sims, 1964). This is evidenced by nonclinical studies using glutathione depletion rodent models that are more sensitive to APAP-induced acute hepatotoxicity than intact rodents (Akai et al, 2007).…”
Section: Introductionmentioning
confidence: 76%
“…In experimental studies, the depletion of GSH is commonly induced by direct inhibition of GSH synthesis enzymes or in knockout models (Akai et al 2007; Wu and Cederbaum 2004). However, in general populations living in chemical-contaminated societies, a more common mechanism for GSH depletion may be GSH consumption through conjugation with chemicals or their metabolites.…”
Section: Dna Hypomethylation Through a Unifying Mechanismmentioning
confidence: 99%